Optimizing Organizational Structure in the Muhammadiyah Student Association at Senior High Schools - Widyastuti, Rini; Siswanto, Deny Hadi; Pisriwati, Siti Atwano; Alam, Sri Rahayu (Journal of Social and Community Development, 2024)
This research delves into the background provided and aims to uncover effective strategies for managing the Muhammadiyah Student Association in schools, to foster strong relationships between educational institutions and the community. The study employs a qualitative method with a descriptive approach. Data were gathered through descriptive studies, documentation related to student activities and the Muhammadiyah Student Association, and interviews with several informants. These informants included the Trustees of the Muhammadiyah Student Association, the Muhammadiyah Student Association Management Committee, and members of the Muhammadiyah Student Association at Muhammadiyah Mlati High School. Data collection techniques comprised interviews and documentation. The findings indicate that while the management of the Muhammadiyah Student Association at Muhammadiyah Mlati High School has been implemented, it has not yet reached an optimal level. This is attributed to existing weaknesses in the management process and the underutilization of available strengths and opportunities.